The new corporate enclosures: Plantation forestry, carbon markets and the limits of financialised solutions to the climate crisis. (November 2016) - Richards, Carol; Lyons, Kristen
Highlights: Explores the claims-making activities associated with the financialisation of land and natural resources. Focuses upon a transnational land acquisition from Norway to Uganda. Employs a unique methodology following capital an examining 'both ends' of the land deal simultaneously. Considers the nexus of an expanding carbon economy and land acquisition in terms of new corporate enclosures. It is argued that despite claims of economic development, finance-driven enclosures have serious negative effects on local communities. Abstract: In recognition of the opportunities associated with climate change, the finance sector have engaged in market based activities via the acquisition of land for ecosystem services, such as biofuel production or forestry for carbon sequestration. Many of these investments are global in scope; with finance capital from the Global North directed into the acquisition of land in the global South. We take the case study of the self-proclaimed largest plantation forestry operator on the African continent, the Norwegian company, Green Resources and their Ugandan land acquisition, to explore, firstly, the claims-making associated with the expanding financialisation of land and natural resources and secondly, the new corporate enclosures engendered via such companies' participation in the expanding carbon economy. Our findings show that investor claims regarding the economic development and environmental sustainability at the site level do not match with the lived reality of Ugandan villagers at the investment site. Whilst carbon capture is possible, it is outweighed by a suite of social and environment ills, including forced dispossession, biodiversity loss and chemical pollution.